Modified multiplying matrix for Galois field GF(2m) multiplier structural complexity evaluation - Hlukhova, Aleksandra (Lviv Polytechnic Publishing House, 2015)
Method of structural complexity estimation of modified multiplying matrix with ordered structure is proposed. The method is based on total length of connections inside multiplying matrix calculation. Matrix with ordered structure allows a partition to the same sub-matrix. One submatrix can be serially used for multiplication instead of one large unmodified matrix. Multiplier structural complexity can be reduced more than 100 times.
Keywords: Galois field GF(2m); Gaussian normal base of type 2; scalable multiplying; core generator; structural complexity